Vibration attenuation characteristics of finite locally resonant meta beam: Theory and experiments. (1st March 2023) - Patro, Somya Ranjan; Banerjee, Arnab; Ramana, G.V.
Abstract: Dynamic vibration absorbers are of utmost importance in civil and mechanical engineering applications; however, their intricate mechanisms are always challenging for practical realization. This paper investigates the vibration suppression characteristics of a base-excited cantilever beam having a series of lumped masses and spring–mass resonator systems. Both analytical and experimental investigations are carried out to compare the transmittance of the dynamic displacement response of the entire system. In the analytical method, a single unit cell comprises an Euler Bernoulli beam attached by a lumped mass and a spring–mass resonator (SMR) system. The transfer matrix method establishes the force–displacement relationship between each unit cell. Furthermore, experiments were conducted by applying a monochromatic frequency to the beam and detecting transmitted vibrations at the beam and SMR systems. The experimental results are validated with the analytical results, providing essential confidence in our proposed methodology. Moreover, several parametric studies were also conducted to obtain the rationale for the variation in the number and location of SMR systems in the vibration characteristics of the entire system. Highlights: Dynamic analysis of beams having resonators and lumped masses is studied. Analytical and experimental studies are done to calculate transmittance parameters. Dynamic response of each resonator is obtained experimentally. Comparison of the bandgap is done between single and multiple resonators. Variation of bandgap is observed in meta beam with the position of lumped mass.